2012
DOI: 10.1117/12.930486
|View full text |Cite
|
Sign up to set email alerts
|

Initial on-orbit radiometric calibration of the Suomi NPP VIIRS reflective solar bands

Abstract: The on-orbit radiometric response calibration of the VISible/Near InfraRed (VISNIR) and the Short-Wave InfraRed (SWIR) bands of the Visible/Infrared Imager/Radiometer Suite (VIIRS) aboard the Suomi National Polar-orbiting Partnership (NPP) satellite is carried out through a Solar Diffuser (SD). The transmittance of the SD screen and the SD's Bidirectional Reflectance Distribution Function (BRDF) are measured before launch and tabulated, allowing the VIIRS sensor aperture spectral radiance to be accurately dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…It was later identified that the wavelength dependent optics degradation was caused by the RTA mirror contamination [13][14][15] . Illustrated in Figure 10 (left) is an example of VIIRS sensor response trending for bands M1-M5 and M7.…”
Section: Optics Degradationmentioning
confidence: 98%
See 1 more Smart Citation
“…It was later identified that the wavelength dependent optics degradation was caused by the RTA mirror contamination [13][14][15] . Illustrated in Figure 10 (left) is an example of VIIRS sensor response trending for bands M1-M5 and M7.…”
Section: Optics Degradationmentioning
confidence: 98%
“…This degradation is wavelength, mirror side, and mirror scan-angle dependent [7][8] . Due to coating contamination, VIIRS rotating telescope assembly (RTA) mirrors have experienced more degradation in the NIR and SWIR spectral region [13][14][15] . Because of this wavelength-dependent optics degradation, the sensor's relative spectral response (RSR) or spectral response function (SRF), combined with in-band (IB) and out-of-band (OOB) responses, needs to be adjusted or modulated.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to (5), we have the following equation which relates the BRDF degradation factor at a later orbit 2 t with its value at an earlier orbit 1 t only use half-angle-mirror (HAM) side A, high gain stage for dual gain bands, and mid-detector for each band (detector 8 for the M-bands and 16 for the I-bands). In the equation, B λ indicates the central wavelength of the band, B indicates a particular band, RVS is the relative reflectivity of the HAM (side A) 12 , RTA H is the BRDF degradation factor at the RTA SD view angle, and F is the detector F-factor 13,14 . As we did in the last section, we select t 1 that is small enough so that the SD BRDF degradation factor is angle independent.…”
Section: Sd Brdf Degradation Factor Angular Dependence Determined Fromentioning
confidence: 99%
“…At each scan, data were collected at all three calibration views. The TEB are calibrated per scan with the BB source, and the RSBs are calibrated once per orbit over the South Pole when the SD is fully illuminated [15]. The SD source is monitored by the onboard Solar Diffuser Stability Monitor to track changes in the SD reflectivity [16].…”
Section: B Obcsmentioning
confidence: 99%